Local fractional variational iteration algorithm II for non-homogeneous model associated with the non-differentiable heat flow - Zhang, Yu; Srivastava, Hari M; Baleanu, Mihaela-Cristina (Advances in mechanical engineering, 2015)
In this article, we begin with the non-homogeneous model for the non-differentiable heat flow, which is described using the local fractional vector calculus, from the first law of thermodynamics in fractal media point view. We employ the local fractional variational iteration algorithm II to solve the fractal heat equations. The obtained results show the non-differentiable behaviors of temperature fields of fractal heat flow defined on Cantor sets.